Características da camada limite atmosférica marinha em cruzeiros oceanográficos realizados no Atlântico Sul e Equatorial - Rossato, Fernando (2019)
A study of sensible (H) and latent (Le) heat fluxes between the ocean and the atmosphere, using measurements performed by micrometeorological towers aboard Brazilian research vessels in the South and Equatorial Atlantic Ocean, is presented. Data obtained from four cruises, performed in December 2012, July and October 2015 and between November 2017 and January 2018, were studied. The heat fluxes obtained from the Eddy Covariance (CV) methodology and the bulk parameterization were analyzed and compared. For the cruises performed in December 2012, July 2015 and October 2015, the largest differences in fluxes were observed associated with the passage of low pressure atmospheric systems, large differences between sea temperature and air temperature and strong winds. The greatest similarities between the flows were observed under the influence of the South Atlantic Subtropical High and light winds. For the cruise performed between November 2017 and January 2018, the largest discrepancy between the two methods was observed, compared to other cruises, especially for Le. It was also analyzed the micrometeorological behavior of the flow in each of the cruises, under different stability conditions. Anisotropic turbulence was identified in October 2015. This study presents for the first time Hockey Stick obtained from data collected on moving ships. In addition it was possible to observe the presence of submeso scale movements, with the highest number from November 2017 to January 2018. These movements can influence vertical flows, generating unpredictable and random contributions. The results demonstrate the importance of local ocean surface conditions and the large-scale synoptic conditions of the atmosphere, which influence the evolution of the marine atmospheric boundary layer and the heat transfer between the ocean and the atmosphere.